Cesarean scar pregnancy - Hanáček, Jiří; Heřman, Hynek; Křepelka, Petr; Hašlík, Lubomír; Brandejsová, Anna; Krofta, Ladislav (Ceska gynekologie, 2022)
OBJECTIVE: To summarize the current knowledge on pregnancy in a cesarean scar. METHODOLOGY: A literature review on the topic using the PubMed database. RESULTS: Gravidity in a cesarean scar is a relatively new type of ectopic pregnancy that will be an increasingly common problem in an era of increasing cesarean section rates. It is still a relatively rare event, occurring in about 6% of the population. Diagnosis is based primarily on ultrasound examination and is essential early on in pregnancy. The pathogenesis of the disease is due to a disorder of the basal layer of the endometrium and can lead to conditions that we refer to as placenta accreta spectrum. The management is completely individualized and depends on hCG values, ultrasound findings, fetal viability, the wishes of the pregnant woman and the experience of the gynecologist concerned. CONCLUSION: This is still a rare occurrence of ectopic pregnancy but with increasing potential. The solution is completely individualized based on a precise and early ultrasound diagnosis.
Keywords: Cesarean Section; Cicatrix; těhotenství; jizva; vacumaspiration; Humans; mimoděložní těhotenství; Methotrexate; placenta accreta spectrum; placenta accreta; ultrasound diagnosis; methotrexate; Pregnancy, Ectopic; uterine scar resuture; ženské pohlaví; císařský řez; Placenta Accreta; cesarean scar pregnancy; lidé; Pregnancy; Female